2020
DOI: 10.1111/tid.13384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID‐19 on liver transplantation in Korea

Abstract: ™MERS(Middle East Respiratory Syndrome) outbreak is a unique case of infection occurred in Korea 2015. The first infected person was a 68-year-old man who returned from a business trip in the Middle East, and by November, there had been a total of 186 patients and 38 deaths. Two infected people died in the first

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Other centers in areas where COVID-19 prevalence was low – or the infection reached its peak slowly – have continued their activity at a routine or even increased rate compared to 2019, being able in some cases to shunt COVID-19 affected patients elsewhere[ 17 - 20 ].…”
Section: Trends In Organ Donation and Transplant Activity During The mentioning
confidence: 99%
See 2 more Smart Citations
“…Other centers in areas where COVID-19 prevalence was low – or the infection reached its peak slowly – have continued their activity at a routine or even increased rate compared to 2019, being able in some cases to shunt COVID-19 affected patients elsewhere[ 17 - 20 ].…”
Section: Trends In Organ Donation and Transplant Activity During The mentioning
confidence: 99%
“…However, some centers have continued this practice even in high COVID-19 prevalence regions by creating COVID minimal-exposure pathways and reported favorable outcomes[ 3 , 22 , 23 ]. Surprisingly, data from South Korea showed that LDLT – the main type of transplantation performed in this county – did not significantly decrease even during the peak of the epidemic, thanks to a strict screening and tracing policy based on the experience of the previous Middle Eastern Respiratory Syndrome Coronavirus (MERS-CoV) infection[ 20 ].…”
Section: Living Donor Liver Transplantation Activity During the Pandementioning
confidence: 99%
See 1 more Smart Citation
“…This effect was predominant in the beginning of the pandemic, improving somewhat after the centers established segregated patient flows to avoid cross‐contamination. 4 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the COVID-19 pandemic was reported to have had a similarly severe impact on transplant medical care, with the number of referrals of potential donors decreasing by 39% in the United Kingdom [ 36 ] and the number of potential deceased organ donors decreasing by 16% in comparison with previous years in France [ 37 ]. Conversely, in South Korea, (as in Japan), where the COVID-19 pandemic manifested relatively early with a less impact than in the United States and Europe, there was no significant change reported in the number of liver transplantations or kidney transplantations as of March and April, 2020 [ 38 , 39 ], respectively, from the previous year, for both living donor transplants and BDD transplants. These findings showed that the ability to perform organ transplantation is dependent on the severity of the spread of COVID-19 in a given country; however, as these reports relate to the situation in spring 2020, subsequent reports on the overall situation of organ transplantation in 2020 are awaited.…”
Section: Discussionmentioning
confidence: 99%